2006
DOI: 10.1177/0266242606067270
|View full text |Cite
|
Sign up to set email alerts
|

Succession Planning in SMEs

Abstract: This study reports the results from a survey of 368 family-owned small to medium size enterprises (SMEs) with regard to the importance, nature, and extent of succession planning. By categorizing SMEs according to their annual revenues, total number of employees, and number of family members employed within the firm, significant differences were found between larger and smaller firms. Consistent with extant literature, the findings reveal that most family members join the firm for altruistic reasons. Issues rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 63 publications
(107 reference statements)
6
87
0
2
Order By: Relevance
“…Succession planning is a systematic process of recognizing and developing future business leaders to grow competitive advantage-based knowledge. Successful succession planning is a critical issue for SMEs [47]. To perform better, a firm needs more than resources and capabilities; it also requires the tacit knowledge that is embedded in firm's routine in order to successfully coordinate and mobilize existing and future resources and capabilities [39].…”
Section: Managerial Capabilitymentioning
confidence: 99%
“…Succession planning is a systematic process of recognizing and developing future business leaders to grow competitive advantage-based knowledge. Successful succession planning is a critical issue for SMEs [47]. To perform better, a firm needs more than resources and capabilities; it also requires the tacit knowledge that is embedded in firm's routine in order to successfully coordinate and mobilize existing and future resources and capabilities [39].…”
Section: Managerial Capabilitymentioning
confidence: 99%
“…In their research, [50] found that business transitions occur more smoothly when the heirs are better prepared, and post-transition performance is positively affected by the heirs' education level. The preparation of a competent leader is also seen as an important part of succession planning, which is expected to improve the probability of the success of the transition process [27,50,51,59] and refers to the deliberate and formal process that facilitates the transfer of ownership and management control. The process of preparing a competent leader should also include knowledge transfer between family generations [57] as the transfer of tacit knowledge from a founder to a successor has been identified as one of the key processes in developing and protecting knowledge and guaranteeing the continuity of a family business [7].…”
Section: Effectiveness Of Family Business Successionmentioning
confidence: 99%
“…Succession is described as "the lengthiest strategic process for family firms" (Barach and Ganitsky, 1995, p. 131). It is considered to be a slow multistage process that involves an increasing participation of the successor and a decreasing involvement of the predecessor until the real transfer takes place (Churchill and Hatten, 1987;Cabrera-Suarez et al, 2001;Motwani et al, 2006). Succession is so central and crucial to the existence of the family firm that Ward (1987) defines a family business as a business that will be passed on from generation to generation.…”
Section: Knowledge As An Enabler Of Longevity In Family Businessmentioning
confidence: 99%